LEXICOGRAPHICAL PORTRAIT OF THE WORD BILINGUISM - Yuldasheva Shakhrizoda Salimovna; Shadieva Dilrabo Kurbanovna (American Journals Publishing, 2023)
The article deals with the study of new borrowed words in the modern Russian language, including the lexicographic portrait of a new word and the reasons for its creation.
Keywords: lexicography, fundamental changes in the new formation of the language, the problem of borrowing, the logical connection of words, the study of the consequence.